اعداد تمرينات خاصة بحاجز مصمم وتاثيرة في بعض المتغيرات البدنية والميكانيكية وانجاز 100 متر حواجز نساء - بكي, منى زيدان (Sulaimani Journal for Humanities, 2018)
Summary For the purpose of access to higher achievement in any tournament for the purpose of achieving the record to reach high levels in all sports fields should be linked to a complete and connected to a series of measures that build on the scientific bases in how to choose the players to complete the educational process of training and achievement levels Alahomn possible to benefit from the principles of Albaao mechanical in all sports when training for the development of motor performance and the form in which it serves the purpose of performance so mechanical Valmngarat any performance provides the right foundation for coach and teacher, and innovative designs to Hador in the development of motor performance because it is considered reshape ideas and formulation of applied science and design one of the key processes for technology learning and as athletics affected the evolution of the level of the physical and mechanical variables as the practice of asking athletics upgrade these capabilities to the record, it turned out this event 100m hurdles Amamcklh research is led weakness in the level of records to accomplish the 100-meter hurdles women to Tsalat about the nature of the performance of the players mechanically for this event and through follow-up tournaments noticed researcher weak performance mechanically and weakness in some of the physical variables in terms of passing non-good due to the payment of the good of others strength and distance pivot the front is To correct this researcher considered a design serve to improve motor track and improve achievement thus Find a target: 1- Design barrier to prepare special exercises to effectively 100m hurdles for the research sample 2- Prepare special exercises in the development of some physical and mechanical variables Presumably search 1- There are significant differences between the before and after tests in physical variables for a sample search 2- There are significant differences between tribal and dimensional tests in mechanical variables differences. Part II contains Alcnametekih physical concepts and capabilities used in the research, design concept and stages of motor performance. The third chapter included the research methodology used and the sample of the research and the homogeneity of the sample and the devices used in research, design and methodology of the user and the user has the researcher used statistical bag in the extraction of statistical results And Part IV contains the results before and after the tests The Part V contains the most important conclusions and recommendations, where the researcher concluded that the user design has been instrumental in improving motor performance to sample either the recommendations researcher recommends ipso facto affect other designs to improve performance level and then achievement.